Frequently Asked Questions About Huanglongbing (HLB; citrus greening) for Homeowners - Brooke L. Moffis; Jamie D. Burrow; Megan M. Dewdney; Michael E. Rogers (EDIS, 2016)
Huanglongbing (HLB), also known as citrus greening, is a serious bacterial disease that affects citrus in Florida. Florida residents enjoy growing citrus for a variety of reasons, but growing citrus in today’s disease climate is not an easy task. This 7-page document is designed to help Master Gardeners and homeowners answer commonly asked questions about HLB. Written by Brooke L. Moffis, Jamie D. Burrow, Megan M. Dewdney, and Michael E. Rogers and published by the Plant Pathology Department, May 2016.